Formulation and Physical Evaluation of Face Toner from Dayak Onion (Eleutherine bulbosa) Extract as Anti-Acne - Basyir, Ahmad; Kustiawan, Paula Mariana (Fakultas Farmasi, Universitas Surabaya, 2026)
Acne is a skin disorder caused by inflammation due to bacterial infections such as Staphylococcus aureus. Dayak onion (Eleutherine bulbosa) is known to contain active compounds such as flavonoids, saponins, tannins, and triterpenoids that have antibacterial potential. This study aims to formulate and evaluate a toner preparation from E. bulbosa ethanol extract as an anti-acne agent. Five toner formulations with varying extract concentrations (0%, 0.5%, 0.75%, 1%, and 1.5%) were prepared and tested for physical characteristics (organoleptic properties, homogeneity, pH, viscosity) and antibacterial activity against S. aureus using the disk diffusion method. The antibacterial test showed that an increase in extract concentration was directly proportional to an increase in the inhibition zone diameter against S. aureus, with Formula 4 (1.5%) exhibiting the highest inhibition power of 17.2 mm (p<0.05). Thus, E. bulbosa extract can be formulated as toner. Further optimization is required to enhance its effectiveness as an anti-acne product.